The Danish Vascular Registry, Karbase - Eldrup N (Clinical Epidemiology, 2016)
Nikolaj Eldrup,1,2 Charlotte Cerqueira,3 Louise de la Motte,2,4 Lisbet Knudsen Rathenborg,2,4 Allan K Hansen2,5 1Department of Cardiothoracic and Vascular Surgery, Aarhus University Hospital, 2Karbase, The Danish Vascular Registry, Aarhus, 3Registry Support Centre (East) – Epidemiology and Biostatistics, Research Centre for Prevention and Health, Capital Region of Denmark, 4Department of Vascular Surgery, Rigshospitalet, Copenhagen University Hospital, Copenhagen, 5Department of Vascular Surgery, Aalborg University Hospital, Aalborg, Denmark Aim: The Danish Vascular Registry (DVR), Karbase, is monitoring arterial and advanced vein interventions conducted at all vascular departments in Denmark. The main aim of the DVR is to improve the quality of treatment for patients undergoing vascular surgery in Denmark by using the registry for quality assessment and research. Study population: All patients undergoing vascular interventions (surgical and endovascular) at any vascular department in Denmark are registered in the DVR. The DVR was initiated in 1989, and each year, ~9,000 procedures are added. By January 2016, .180,000 procedures have been recorded. Since 2001, data completeness has been .90% (compared to the Danish National Patient Register). Main variables: Variables include information on descriptive patient data (ie, age, sex, height, and weight) and comorbidity (ie, previous cardiovascular disease and diabetes). Process variable includes waiting time (time from event to medical contact and treatment) and the type of procedures conducted. Outcome variables for in-hospital complications (ie, wound complications, myocardial infarction, stroke, amputation, respiratory complications, and renal insufficiency) and 30-day patency are submitted. Variables for medical treatment (antithrombotic and statin treatment), amputation, and survival are extracted from nationwide, administrative registers. Conclusion: The DVR reports outcome on key indicators for monitoring the quality at all vascular departments in Denmark for the purpose of quality improvement. Furthermore, data are available for research and are being used in international collaborations on changes in clinical practices. Keywords: vascular surgery, quality of care, clinical registry